Death Khairat Fund Principles and Practice In Kota Damansara Mosque According To Hifz Al-Mal - Zawin Hannan Sofea Shahbuddin; Setiyawan Gunardi; Azman Ab. Rahman; Ahmad Zaki Salleh; Syed Mohd Najib Syed Omar; Khairunneezam Mohd Noor (USIM Press, 2024)
Journal of Fatwa Management and Research (JFatwa) Volume 28 No.3 Page (71-81)